Dilemmas of upbringing in the 21st century versus a balanced development - Strumińska-Doktór, Anna (Studia Ecologiae et Bioethicae, 2008)
Among the contemporary dilemmas connected with the upbringing, the issue of responsibility for oneself, for others and for the environment in which we live is particularly important, therefore, upbringing cannot be separated from life. It can be interpreted as the entirety of human actions aimed at shaping a human being for responsible fulfillment of roles in family and society. The contemporary generation has a vital task to perform. It should try to remedy the surrounding reality, the change of habits and attitudes of the next generation depends on the educators’ fresh outlook on the upbringing , the previous educational system did not meet the hope s pinned on it, and related to developing an ecological awareness. Only education enables bringing the relationships existing in the environment closer. Schools initiate many actions in the field of environmental education. Sadly, the commitment of schools varies greatly and is determined by the activity level of the individual teachers, who are not responsible for the implementation of the environmental topics, the lack of supervision over the introduction of questions from this field and the lack of a person responsible, delay education and upbringing for the eco-development. It is the hands of the young generation that taking up actions rests in; actions which are not harmful and can even save the closest environment, the role of upbringing in this scope cannot be overestimated.